Correction: Spironaphthoxazine switchable dyes for biological imaging. Issue 15 (29th March 2018) - Xiong, Yaoyao; Jentzsch, Andreas Vargas; Osterrieth, Johannes W. M.; Sezgin, Erdinc; Sazanovich, Igor V.; Reglinski, Katharina; Galiani, Silvia; Parker, Anthony W.; Eggeling, Christian; Anderson, Harry L.
Abstract : Correction for 'Spironaphthoxazine switchable dyes for biological imaging' by Yaoyao Xiong et al., Chem. Sci., 2018, 9, 3029–3040.